2017
DOI: 10.1108/jes-07-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the volume and structure of alcohol consumption in Russian regions

Abstract: Purpose -The purpose of this paper is to examine macroeconomic factors that are significantly related to consumption of various alcoholic beverages in Russia. Design/methodology/approach -The authors consider 78 Russian regions for the period from 2008 to 2012. Data were collected from the Federal State Statistics Service of Russia. The authors investigate differences in the volume and structure of consuming absolute alcohol in aggregate, vodka, beer, and wine. Estimating fixed effect panel models enables us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…However, existing academic scholarship suggests that alcohol abuse may escalate during economic recovery. Kossova et al (2017) found that alcohol consumption is procyclical in Russia, which is consistent with the findings of Ruhm and Black for the US (Ruhm and Black, 2002), Johansson et al for Finland (Johansson et al, 2006), and Ásgeirsdóttir et al for Iceland (2014). Thus, there is an additional challenge for the public policy expressed in the need to combat alcohol abuse while improving macroeconomic conditions, rising household incomes, and reducing unemployment.…”
Section: Discussion and Policy Implicat Ionssupporting
confidence: 86%
See 1 more Smart Citation
“…However, existing academic scholarship suggests that alcohol abuse may escalate during economic recovery. Kossova et al (2017) found that alcohol consumption is procyclical in Russia, which is consistent with the findings of Ruhm and Black for the US (Ruhm and Black, 2002), Johansson et al for Finland (Johansson et al, 2006), and Ásgeirsdóttir et al for Iceland (2014). Thus, there is an additional challenge for the public policy expressed in the need to combat alcohol abuse while improving macroeconomic conditions, rising household incomes, and reducing unemployment.…”
Section: Discussion and Policy Implicat Ionssupporting
confidence: 86%
“…Since the mid-2000s, these factors no longer exert a decisive influence on the gender gap in life expectancy, since Russia has been experiencing macroeconomic and political stabilisation. Furthermore, there has been a change in the structure of alcohol consumption over the past ten years in Russia (Kossova et al, 2017). Consumption of strong alcohol (vodka) is partially replaced by low-alcohol beverages (beer).…”
Section: Determinants Of the Ge Nder Gap In Life Expectancymentioning
confidence: 99%
“…Secondly, in line with [14], trade openness is included in the model. Thus, a tradition for high levels of trade facilitates and opens up a more differentiated supply of goods.…”
Section: Resultsmentioning
confidence: 99%
“…Deveaux and Sassi use data for twenty OECD countries and find a stability in the overall alcohol consumption levels [13], but, for example, young adults show increasing higher-risk drinking behaviour, and such factors will in the longer run have influence on the structural composition of alcohol consumption. For Russia, a study by Kossova et al also finds specific internal factors to be of importance for the structure of alcohol consumption, where e.g., unemployment is, somewhat surprisingly, negatively related to the consumption of vodka and beer, but in some years positively related to wine consumption [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Differences in alcohol consumption are evident not only at the level of countries or regions (Branstrom & Andreasson, 2008;Bencevic-Striehl et al, 2009), but also in connection with the place where alcohol consumption takes place (Callinan et al, 2016) or the type of alcoholic beverage (Kossova et al, 2017). The consumption of individual types of alcoholic beverages poses different risks.…”
Section: • 1 Introduction and Theoretical Backgroundmentioning
confidence: 99%